Kalatea Kids “Inovasi Teh Herbal Patikala Aman dan Edukatif untuk Anak Usia Dini” - Hikrawati; Putri Kirana Aswadi; Kurnia Salsabila; Insan Safitri (Kilau Publishing, 2026)
The current development of the food industry demands innovation in healthy beverages, especially for early childhood who are in a period of growth. One of Indonesia's local plants rich in benefits but not yet widely utilized is Etlingera elatior, better known as Patikala. This plant has properties as an antioxidant, anti-inflammatory, and helps boost the immune system. Kalatea Kids is presented as an educational herbal tea product based on Patikala, specially formulated for early childhood. Not only offering health benefits, Kalatea Kids is also designed as an educational tool through illustrated interactive packaging, bright colors, and simple moral messages. This product is targeted as a healthy alternative to artificially sweetened beverages, while also introducing children to local herbal plants from an early age. Promotion and distribution are carried out through social media and PAUD (Early Childhood Education) communities. The product is packaged in tea bag form with child-friendly materials, caffeine-free, and processed hygienically. It is hoped that Kalatea Kids will become a healthy beverage product that is not only safe, but also encourages local plant literacy and a healthy lifestyle from an early age.